The Liquid Waste Management Of Tapioca Miniplant In Negara Bumi Ilir Center Of Lampung - Atmodjo M C T (Bandar Lampung University (UBL), 2017)
The Liquid Waste of Tapioca Plant needs work hard for liquid waste application for us with circumstance friendly . The design of mini pool with 12 m in volume close to miniplant and make 3 inch dia. of PVC pipe as channel to Waste Water Treatment Plant (WWTP) is one of the waste solution. The WWTP has 700 m3 of anaerobic digester for biogas process. The Biogas yield collected in biogas tank which able to use for cooking stove and lamp for light. The liquid waste from WWTP can be use for irrigation and the sludge able to use for fertilizer. Key words : Biogas, Liquid waste, Tapioca miniplant, digester.